2021
DOI: 10.3389/fonc.2021.665291
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Metabolism in the Development of Personalized Therapies in Acute Myeloid Leukemia

Abstract: Despite significant recent advances in our understanding of the biology and genetics of acute myeloid leukemia (AML), current AML therapies are mostly based on a backbone of standard chemotherapy which has remained mostly unchanged for over 20 years. Several novel therapies, mostly targeting neomorphic/activating recurrent mutations found in AML patients, have only recently been approved following encouraging results, thus providing the first evidence of a more precise and personalized approach to AML therapy.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 98 publications
0
4
0
Order By: Relevance
“…1 mitochondrial functions such as BCL2 family members [23,[28][29][30][31]. Metabolic adaptations in AML have been reported to entail rewiring of carbon and nitrogen fluxes that promote mitochondrial respiration and redox homeostasis [15,[35][36][37][38]. Studies using patient-derived xenograft (PDX) models revealed that araC-resistant AML cells overexpress genes driving OX/PHOS [39,40], whereas murine syngeneic AML models have shown that residual cells increase the uptake of glutamine and aspartate to fuel OX/PHOS and synthesize pyrimidine and glutathione [41], which may represent adaptations required to survive in that context.…”
Section: Introductionmentioning
confidence: 99%
“…1 mitochondrial functions such as BCL2 family members [23,[28][29][30][31]. Metabolic adaptations in AML have been reported to entail rewiring of carbon and nitrogen fluxes that promote mitochondrial respiration and redox homeostasis [15,[35][36][37][38]. Studies using patient-derived xenograft (PDX) models revealed that araC-resistant AML cells overexpress genes driving OX/PHOS [39,40], whereas murine syngeneic AML models have shown that residual cells increase the uptake of glutamine and aspartate to fuel OX/PHOS and synthesize pyrimidine and glutathione [41], which may represent adaptations required to survive in that context.…”
Section: Introductionmentioning
confidence: 99%
“…Although specific mutations can dictate selective metabolic vulnerabilities( 44 ), metabolic dependencies can be present across multiple genetic backgrounds as a phenotype bottleneck i.e. a state essential for continued tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, AML cells show dependence on FAO, even in the absence of treatment exposure, due to low levels of prolyl-hydroxylase 3 (PHD3), which is an activator of acetyl-CoA Carboxylase 2 (ACC2) that normally suppresses FAO. Furthermore, high expression levels of carnitine palmitoyl transferase 1A (CPT1A) and the carnitine transporter CT2 (SLC22A16) also contribute to promoting FAO and constitute therapeutic targets for AML subsets [23][24][25]. Very recently, LICs from relapsed/refractory (R/R) AML patients have been found to be different metabolically from the LICs of de novo AML patients [26].…”
Section: Deregulated Metabolic Programs In Leukemia 21 Glucose Metabolism: Warburg Effect and Metabolic Flexibilitymentioning
confidence: 99%